La colaboración mediada por tecnología como estrategia para potenciar visitas guiadas : El caso del Centro Interactivo de Ciencia y Tecnología abremate, desde la mirada de sus actores - Dávila, Analía Roxana (2020)
It is proposed to analyze the scope and limitations that Information and Communication Technologies (ICTs) offer as collaboration mediators; and enhancers of innovative experiences in non-formal education spaces. To this end, it is proposed to implement a methodology mediated by ICTs to promote and achieve greater use of the guided visits to the interactive science and technology centers. The work contemplates, firstly, carrying out a bibliographic inquiry and background review of interactive science and technology centers in different Ibero-American countries and secondly, it is proposed to design a methodology to enhance collaboration mediated by technologies in the framework of visits to centers interactives and then apply this methodology to a particular case study to measure its impact. The experience will take place at the Open Science and Technology Interactive Center (CICyT) of the National University of Lanús and proposes, through a specific intervention, comparatively analyzing 3 types of guided visits: a) traditional in-person visit format, b) visit face-to-face with instance of collaboration activities without the use of technology, c) interaction mediated by ICTs prior to the visit, face-to-face visit with use of ICTs, and instance of interaction mediated by ICTs after the visit, which will then be contrasted with the antecedents and theoretical studies found in the bibliography.